Students’ Perception toward Good Lecturer Pedagogical Competence - Andi Asrifan; Ali Wira Rahman; Raveenthiran Vivekanantharasa; K.J Vargheese; Muhammad Shoaib Khan Pathan; Gül Erkol Bayram (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
As the application of the four competencies for the lecturers in teaching and learning becomes a new business for them to fulfil those competencies (pedagogical, professional, personality, social). This impacts the provision of a new method for students in learning activities so that a teacher could develop a curriculum per the respective educational unit and the local needs of each student. The first pedagogical competence deals with a lecturer's ability to manage the classroom and facilitates the students’ diversity. Sometimes lecturers apply different pedagogic actions to students' perceptions so that what is supposed to be good by lecturers sometimes inversely with students’ intake. This study aimed to facilitate the students' perception regarding the pedagogical perception of a good lecturer. The result is supposed to be some consideration from the lecturer in applied pedagogical action in the classroom.